O4 Hiv incidence among people who attend sexual health clinics in england in 2012: estimates using a biomarker for recent infection. (18th May 2015) - Aghaizu, Adamma; Murphy, Gary; Tosswill, Jennifer; DeAngelis, Daniela; Charlett, Andre; Gill, Noel; Moses, Samuel; Ward, Helen; Hughes, Gwenda; Delpech, Valerie
Abstract : Introduction: In England, 80% of HIV diagnoses are in sexually transmitted infection (STI) clinics. Since 2009, Public Health England offered testing for recent HIV infection. Aim: To estimate HIV incidence among STI clinic attendees in 2012. Methods: The AxSYM avidity assay, modified to determine antibody avidity, was conducted on aliquots of newly diagnosed persons and results linked to the national HIV database. An incident case was defined as avidity <0.8, no antiretroviral treatment or AIDS and viral load ≥400 copies/mL at diagnosis. The number of persons tested for HIV was assessed using the Genitourinary Medicine Clinic Activity Dataset. We estimated and adjusted for a 1.9% (95% C.I. 1.0%–3.4%) false recent rate and used 202 days as the mean duration of recent infection to calculate incidence rates. Results: Of 212 STI clinics in England, 150(71%) submitted specimens for recent infection testing, comprising 3, 930 persons newly diagnosed; 50% were MSM. The number of HIV tests/diagnosis was 210 for all clinic attendees, 38 for MSM, 403 for all heterosexuals and 46 for black African heterosexuals. HIV incidence was 0.15% (95% C.I. 0.13–0.18%) for all attendees, 1.22% (95% C.I. 1.07–1.42%) for MSM, 1.41% (95% C.I. 1.21%-1.66%) for MSM in London, 0.03% (95% C.I. 0.02–0.04%) for heterosexuals and 0.13% (0.05–0.22%) for black African heterosexuals. Discussion/conclusion: Testing for recent HIV infection combined with routinely collected clinical data provides robust and timely national estimates of HIV incidence. HIV incidence among MSM and black African heterosexuals attending STI clinics was 40 and nine times higher respectively than among all heterosexuals, and exceeds the WHO-defined elimination threshold of 0.1%.